Plasmodium oocysts respond with dormancy to crowding and nutritional stress - Tibebu Habtewold (Nature Portfolio, 2021)
Abstract Malaria parasites develop as oocysts in the mosquito for several days before they are able to infect a human host. During this time, mosquitoes take bloodmeals to replenish their nutrient and energy reserves needed for flight and reproduction. We hypothesized that these bloodmeals are critical for oocyst growth and that experimental infection protocols, typically involving a single bloodmeal at the time of infection, cause nutritional stress to the developing oocysts. Therefore, enumerating oocysts disregarding their growth and differentiation state may lead to erroneous conclusions about the efficacy of transmission blocking interventions. Here, we examine this hypothesis in Anopheles coluzzii mosquitoes infected with the human and rodent parasites Plasmodium falciparum and Plasmodium berghei, respectively. We show that oocyst growth and maturation rates decrease at late developmental stages as infection intensities increase; an effect exacerbated at very high infection intensities but fully restored with post infection bloodmeals. High infection intensities and starvation conditions reduce RNA Polymerase III activity in oocysts unless supplemental bloodmeals are provided. Our results suggest that oocysts respond to crowding and nutritional stress with a dormancy-like strategy, which urges the development of alternative methods to assess the efficacy of transmission blocking interventions.